2017
DOI: 10.1080/16000889.2017.1339548
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of aerosol-radiation feedback on local air quality during a severe haze episode in Nanjing megacity, eastern China

Abstract: Severe haze events and their radiation feedbacks exert a profound impact on the weather and tropospheric chemistry. Using the on-line-coupled Weather Research and Forecasting with Chemistry (WRF-Chem) model, this study investigates the impacts of direct aerosol-radiation feedbacks on local air quality (i.e. particulate matter and ozone photochemistry) during a severe autumn haze episode in Nanjing megacity, eastern China. Pronounced radiation feedbacks are found for the predictions of meteorological and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…Similar observations of enhancement in aerosol/trace gas concentration by aerosol‐boundary layer interaction were reported by number of studies, especially over East Asia (Ding et al, ; Li et al, ; Quan et al, ; Wang et al, ). Li et al () observed that the surface temperature decreases by 1.1 to 1.4 °C in regions of high aerosol loading (Nanjing City in China), which favored the accumulation of particles (30.5 μg/m 3 ) and gases (NO 2 , 6.0 ppb). Similarly, an increase of average surface PM 2.5 by 140 μg/m 3 over Beijing was reported by Wang et al ().…”
Section: Resultssupporting
confidence: 85%
“…Similar observations of enhancement in aerosol/trace gas concentration by aerosol‐boundary layer interaction were reported by number of studies, especially over East Asia (Ding et al, ; Li et al, ; Quan et al, ; Wang et al, ). Li et al () observed that the surface temperature decreases by 1.1 to 1.4 °C in regions of high aerosol loading (Nanjing City in China), which favored the accumulation of particles (30.5 μg/m 3 ) and gases (NO 2 , 6.0 ppb). Similarly, an increase of average surface PM 2.5 by 140 μg/m 3 over Beijing was reported by Wang et al ().…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, a reduction in PM 2.5 and PM 10 could also lead to an increase in surface O 3 concentrations (Liu et al, 2013;Li et al, 2017). As PM emissions were lower during the lockdown, the higher solar radiation favored O 3 formation (Heuss et al, 2003;Murphy et al, 2007;Wolff et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to photochemical reactions, the heterogeneous chemical processes occurring on the surface of PM 2.5 and aerosols in the atmosphere are also an important way for the interaction between O 3 and PM 2.5 (Meng et al, 1997;Jacob, 2000;Deng et al, 2010;Li et al, 2011). In Nanjing, high concentrations of PM 2.5 (rising from 100 to 250 μg.m −3 ) resulted in a reduction of 130 W.m −2 of the irradiance and a 12% reduction of near-surface O 3 (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that aerosols can scatter and absorb solar radiation to alter the radiative balance of the atmosphere and surface (direct radiative effect), and can serve as cloud condensation nuclei or ice nuclei to affect cloud properties (indirect radiative effect) (Twomey, 1974). These impacts are coupled with atmospheric dynamics to produce a chain of interactions with a large range of meteorological variables that influence both weather and climate (Ramanathan et al, 2001;Huang et al, 2006;Wu et al, 2009;Li et al, 2017d), which will further induce feedbacks on aerosol production, accumulation, and even severe haze pollutions (Petaja et al, 2016;Li et al, 2017b;Li et al, 2017e;Zhao et al, 2017;Gao et al, 2018). Based on multi-year measurements (from 2010 to 2016), Huang et al (2018) found that aerosol radiative effects led to a significant heating in the upper planetary boundary layer (PBL) and a substantial dimming at the surface over North China.…”
Section: Introductionmentioning
confidence: 99%